The study of the energy spectrum of -particles transmitted through thin polymer films - Abildaev, A.Kh.; Shinbulatov, S.K. (Recent Contributions to Physics, 2017)
Experimental results were obtained in the work on the measurement of the energy spectra of a- particles Pu-238 passed through thin polymer films. Landau distributions were obtained for a-particles that passed through the films. Comparison of experimental results with theoretical calculations is carried out. We came to the conclusion that the films are not single crystals, crystalline inclusions constitute an insignificant fraction within experimental errors. In the work, the isotope of plutonium was used for calibration. The first stage is calibration, to adjust the readings of the output value, in our case to adjust the energy spectra. After calibration with the help of element P8-332, we obtain energy spectra of alpha particles. Covering the surface of the source with thin polymer films, we obtain analyzes on the computer. The work consists of several parts. In the first part we obtain the energy spectra of a thin polymer film under the number one. In exactly the same way, in the second part we obtain the energy spectra of alpha particles transmitted through thin polymer films № 2. The work was to determine the composition of polymer films and analyze the energy spectrum. Relying on the results of the study, we can say that the polymer films we are studying are not crystalline films, but rather single crystals, as stated above. In the experiment and in calculations, the difference between our spectra and the Landau distribution is shown. Between the Landau distribution and our experiment, the differences are insignificant and therefore the experimental graphs, that is, the energy spectra, are uniform.